Alive and destroyed a meditation on the Holocaust in time - Francisco, Jason 1967-; Kaiser, Menachem 1985- (Daylight, 2021)
Alive and Destroyed contemplates the long aftermath of the twentieth century’s most notorious crime, drawing on contemporary scholarship, with a focus on dispersed and remote locations in the Holocaust’s vast geography
Keywords: Francisco, Jason -- 1967-; Francisco, Jason; Holocaust, Jewish (1939-1945) / Pictorial works; Documentary photography; Photography, Artistic; Holocauste, 1939-1945 / Ouvrages illustrés; Photographie documentaire; Photographie artistique; documentary photography; art photography; 1939-1945; photobooks; Pictorial works; Photobooks; Livres de photographies; Bildband